2013
DOI: 10.1212/wnl.0b013e31828d57dd
|View full text |Cite
|
Sign up to set email alerts
|

Summary of evidence-based guideline update: Evaluation and management of concussion in sports

Abstract: Objective: To update the 1997 American Academy of Neurology (AAN) practice parameter regarding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
622
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 831 publications
(631 citation statements)
references
References 35 publications
5
622
1
3
Order By: Relevance
“…In children, factors potentially influen cing recovery include age and history of concussions. 27,28 In one study, approximately 90% of young adult male athletes experienced symptomatic recovery within 21 days. 29 However, in an emergency department study of patients aged 11-22 years (including all causes of concussion, not just sports-related), 15% of the sample still exhibited post-concussion symptoms, including headache, dizziness, 'mental fogginess' and depression, 90 days after injury.…”
Section: Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…In children, factors potentially influen cing recovery include age and history of concussions. 27,28 In one study, approximately 90% of young adult male athletes experienced symptomatic recovery within 21 days. 29 However, in an emergency department study of patients aged 11-22 years (including all causes of concussion, not just sports-related), 15% of the sample still exhibited post-concussion symptoms, including headache, dizziness, 'mental fogginess' and depression, 90 days after injury.…”
Section: Recoverymentioning
confidence: 99%
“…42 Young athletes of both sexes are at risk of concussion, but girls report higher concussion rates than boys, particularly in high school and college soccer, basketball, and baseball or softball. 28,[43][44][45] The factors that account for these differences remain uncertain, but might include quality of protective gear, recognition and reporting of concussion symptoms, and neck length and neck muscle strength. 46 Differences in recovery trajectories between males and females are also poorly understood.…”
Section: Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…This includes better concussion education for students entering health professions but also improved education for health care professionals after graduation [10,11]. A study found that only 26.6 percent of general pediatricians were somewhat or very familiar with recently passed concussion legislation and that only 14.6 percent of general pediatricians used concussion consensus guidelines in their practice [12]. An informed primary care clinician can provide crucial anticipatory guidance for safe sport participation, like reminders to wear helmets and use the proper protective equipment.…”
Section: Recommendationsmentioning
confidence: 99%
“…9,2 This attention has led to updated guidelines for reporting and management of concussion or mild traumatic brain injury in athletic competition. 10 These new expectations open the door to challenge the findings of prior prevalence studies from an era where reporting was often minimized to reduce time out of competition. 2 In Marion County, Florida, the athletic director has established guidelines requiring all trainers to document each concussion reported during practice or competition.…”
Section: Introductionmentioning
confidence: 99%